Variation in incidence and survival by ethnicity for patients with myeloma in England (2002–2008). Issue 9 (2nd September 2015) - Samy, E. Faye; Ross, James; Bolton, Edward; Morris, Eva J.; Oliver, Steven E.
Abstract : Incidence and relative survival of myeloma by ethnic group was estimated using data from cancer registries in England (2002–2008). Multiple imputation was used to address missing ethnicity data. In total 24 361 cases of myeloma were identified. Age-standardized incidence rate (ASIR) (per 100 000) was higher in the Black ethnic category at 15.00 (95% confidence interval [CI] 13.50–16.40), than amongst South Asians (ASIR = 5.45, 95% CI 4.76–6.14) or the White group (ASIR = 6.11, 95% CI 6.00–6.22). There was a lower risk of death in the Black group for both 1- and 3-year survival (hazard ratio [HR]1 year = 0.66, 95% CI 0.55–0.79; HR3 year = 0.69, 95% CI 0.58–0.83) and South Asians at 1, 3 and 5 years (HR1 year = 0.65, 95% CI 0.51–0.82; HR3 year = 0.72, 95% CI I 0.57–0.90; HR5 year = 0.68, 95% CI 0.50–0.92) when compared to the White population. Further study of differences in myeloma and precursor biology between population groups is important.